Baixo Sabor concrete arch dam: dynamic monitoring and numerical damage simulation - Álvaro Cunha (2019)
The nowadays-available dynamic monitoring equipment integrating very sensitive low noise sensors creates an opportunity to implement continuously operating dynamic monitoring systems in dams and validate the suitability of these systems to monitor such massive structures with the goal of detecting damage. The detection of abnormal structural behaviour, that may indicate the occurrence of damage, can be based on control charts and is associated with shifts in the modal parameters' values that are not explained by other physical phenomena but a change in the structure's stiffness. To test these statistical tools, modal parameters obtained from real field measured time series may be contaminated with simulated damages. In this context, this paper describes the continuous dynamic monitoring of Baixo Sabor arch dam, which has been carried out by both ViBest/FEUP (Laboratory of Vibrations and Structural Monitoring) and LNEC (National Laboratory for Civil Engineering). Moreover, it is presented the simulation of a set of plausible damage scenarios and their influence in the dam dynamic properties, namely the natural frequencies, with the aim of testing the ability of the said control charts to identify the emergence of abnormal structural behaviour. For this, a numerical model of the dam developed at LNEC's Concrete Dams Department has been used.